Electric‐Field Screening in Atomically Thin Layers of MoS2: the Role of Interlayer Coupling. (1st November 2012) - Castellanos‐Gomez, Andres; Cappelluti, Emmanuele; Roldán, Rafael; Agraït, Nicolás; Guinea, Francisco; Rubio‐Bollinger, Gabino
<x xml:space="preserve">Abstract</x> The electrostatic screening in single and few‐layer MoS2 sheets is studied. Electrostatic force microscopy is used to probe the electric field generated by charge impurities in the substrate and incompletely screened by MoS2 sheets. A non‐linear Thomas–Fermi theory is employed to interpret the experimental results, demonstrating the important role of the interlayer coupling in the screening of MoS2. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>